ECC Based Prevention for Side Channel Attack: A Survey (International Journal of Engineering and Computer Science, 2015)
Elliptic curve cryptography has many advantages like it is used for data encryption as well as digital signature. Also it gives efficiency for both software and hardware implementation. Despite of its security level the elliptic curve cryptography is affected by various types of attacks like side channel attacks. In side channel attack basically the attacker retrieve the secret key with less effort and affect the implementation of the cryptosystem and exploit the information leakage. We introduce the most effective side channel attack is the power analysis attack. This attack categories into simple power analysis attack (SPA) that reveals the secrete key by analyzing operation sequence that depend on the key value using power consumption trace and differential power analysis ie.(DPA) it uses statistical tool for analyzing the correlation between consumption and processing operation which depend on secrete key. Basically the Power analysis attack exploits the power consumption of the cryptosystem and break the ECC.